Effects of the K-value solution schemes on radiation heat transfer modelling in oxy-fuel flames using the full-spectrum correlated K-distribution method. (April 2020) - Liu, Yuying; Liu, Guanghai; Liu, Fengshan; Consalvi, Jean-louis
Highlights: The accuracy of FSCK with different correlated-K solution schemes and RC-FSK in oxy-fuel flames is investigated. A hybrid correlated-K scheme using either the original or the new scheme according to local temperature is proposed. FSCK with the hybrid scheme and RC-FSK demonstrate the best accuracy among these methods. Abstract: Radiation heat transfer in oxy-fuel flames is more important than in conventional fuel-air flames. The Full-Spectrum Correlated K-distribution methods (FSCK) with the original correlated-K solution scheme (Modest and Zhang, 2002) and a newly proposed one (Cai and Modest, 2014), and the Rank Correlated Full-Spectrum K-distribution method (RC-FSK) are used in radiative calculations of oxy-fuel flames. Twelve one-dimensional flames, including fuel-air, dry and wet oxy-fuel flames with various length scales, as well as a two-dimensional dry oxy-fuel flame are studied. The results show that the reference temperature has a non-negligible impact on the accuracy of original scheme and the emission-weighted temperature leads to a good accuracy. The accuracy of the new scheme is almost unaffected by the reference temperature, except for small-scale dry oxy-fuel flames. The error of the new scheme is mainly in the low-temperature region, and its accuracy depends on the length scale of computational domain. A hybrid correlated-K scheme using either the original or the new scheme according to local temperature is proposed. It combines the advantages of two schemes in different temperature regions, and is independent of the reference temperature. In addition, the RC-FSK demonstrates almost the same accuracy as FSCK with the hybrid scheme when the Planck temperature is set equal to the reference temperature.